now,for f(X) to be a factor of p(x) they must have common zeros (meaning if u put p(1) then it must come 0 otherwise f(X) is not a factor but in this case we have to prove so lets just put the value)

p(1)=3*(1^3)-(1)^2-3*1+1

=3*1-2-3+1

=3-2-3+1

=-1

HENCE,X-1 is not a factor

(Disclamiar:ur question is wrong because it should not be given show it should be fin out whether because question is saying to prove that x-1 is factor which means its already factor and needs to be proved)

## Answers ( )

Answer:Step-by-step explanation:let p(x)=3x^3-x^2-3x+1

f(x)=x-1

finding factor of f(x)(meaning finding its root)

x-1=0

x=1

now,for f(X) to be a factor of p(x) they must have common zeros (meaning if u put p(1) then it must come 0 otherwise f(X) is not a factor but in this case we have to prove so lets just put the value)

p(1)=3*(1^3)-(1)^2-3*1+1

=3*1-2-3+1

=3-2-3+1

=-1

HENCE,X-1 is not a factor

(Disclamiar:ur question is wrong because it should not be given show it should be fin out whether because question is saying to prove that x-1 is factor which means its already factor and needs to be proved)

Step-by-step explanation:this is explanation

plzz mark brainlist